WAYS IMPLEMENTATION OF A NEW IDEA IN THE PSYCHOLOGICAL SUPPORT PROGRAM TO IMPROVE SELF-REGULATION DURING MILITARY CONFLICT - KHARCHENKO, V.; KUCHER, D. (Herald of Kyiv Institute of Business and Technology, 2024)
The article considers the need to improve psychological methods of support and rehabilitation of people who have experienced the traumatic effects of war in connection with the military conflict in Ukraine since 2014. The consequences of military actions on the mental health and emotional state of persons participating in the conflict or experiencing its consequences are determined. Individual coping strategies, level of emotion regulation, and willingness to seek psychological support are outlined as key factors in coping with stress and adaptation. Military conflict is a complex socio-psychological phenomenon that affects the psyche and behavior of people, changing their values, beliefs and life orientations. Participants in the conflict and those who directly experience its consequences are faced with revising their life priorities and changing their attitude to risk, which requires the development of effective psychological interventions. Victim assistance organizations focus on the development and implementation of psychological interventions to support and rehabilitate veterans and other victims of war. These initiatives contribute to the formation of psychological support as an important element in strategies for the rehabilitation and social integration of war victims in Ukraine. The development of self-regulation skills is an important element of psychological support and rehabilitation of war victims, as it helps them to effectively adapt to stressful situations and maintain their mental and emotional health. The results of an empirical study, which includes an analysis of stress resistance and social adaptation of conflict participants, are highlighted.